(untitled) (Journal of Scientific Research, 2024)
Pure CaF2 and CaF2:Eu3+ nanoparticles were synthesized by solution combustion method. The structural characterization of the samples was done by XRD (X-ray diffraction). The average crystallite size for CaF2 and CaF2:Eu3+ nanoparticles was found to be 17.11 nm and 32.53 nm respectively. The surface morphology was studied by FESEM (Scanning Electron Microscope) and formation of nanospheroids was observed. The EDAX analysis confirmed the purity of the synthesized samples. The band gap energy of the samples was estimated by UV-Visible Spectroscopy. CaF2 was found as direct band gap material of 3.87 eV and CaF2:Eu3+ as indirect band gap material of 4.99 eV respectively. The photoluminescence excitation peak for CaF2 was observed around 387 nm and the emission peak was observed around 420 nm. The photoluminescence excitation peaks for CaF2:Eu3+ were observed around 299 nm, 317 nm, 361 nm and 394 nm respectively and the emission peaks were observed around 591 nm and 616 nm respectively.